Urban public works in spatial equilibrium: Experimental evidence from Ethiopia - Simon Franklin; Clément Imbertand; Girum Abebe; Carolina Mejía Mantilla (Queen Mary University of London, School of Economics and Finance, 2023)
This paper evaluates a large urban public works program randomly rolled out across neighborhoods of Addis Ababa, Ethiopia. We find that the program increased public employment and reduced private labor supply among beneficiaries and improved local amenities in treated locations. We then combine a spatial equilibrium model and unique commuting data to estimate the spillover effects of the program on private sector wages across neighborhoods: under full program roll-out, wages increased by 18.6%. Using our model, we show that welfare gains to the poor are six times larger when we include the indirect effects on private wages and local amenities.
Keywords: I38; J61; O18; R23; 330; Public works contract; Experiment; Municipal investment; Spatial equilibrium model; Ethiopia; Öffentlicher Bauauftrag; Experiment; Kommunale Investition; Räumliches Gleichgewichtsmodell; Äthiopien